Computer systems : Architecture, networks and communications - Coope, Sebastian (London : McGraw-Hill, 2002)
Highly suitable for modular courses, this book takes account of developments such as the Internet, modern hardware and all aspects or computer systems that are closely interconnected with contemporary courses.
Chapter 1 : Basic Concepts of a Computer System -- Chapter 2 : Number Systems and Data Representation -- Chapter 3 : Digital Logic Circuits and Integrated Circuits -- Chapter 4 : Memory -- Chapter 5 : Computer Software -- Chapter 6 : The Central Processing Unit -- Chapter 7 : Peripherals -- Chapter 8 : File Storage -- Chapter 9 : Building a Small Computer Systems -- Chapter 10 : Interrupts -- Chapter 11 : Data Transfer -- Chapter 12 : Computer Networks -- Chapter 13 : Communication Technologies -- Chapter 14 : Network Types -- Chapter 15 : Communication Protocols -- Chapter 16 : Installing and managing a LAN --
Includes index.
1
Keywords: Computer architecture; Computer network architectures